2011
DOI: 10.1016/j.aju.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Does size matter? The significance of prostate size on pathologic and functional outcomes in patients undergoing robotic prostatectomy

Abstract: BackgroundWe examined the effect of prostate weight on perioperative data, and the pathological and functional outcomes of robotic-assisted laparoscopic prostatectomy (RALP).Patients and methodsData were available from 716 consecutive patients before, during and after undergoing RALP at one institution. Prostate size was arbitrarily stratified by recorded prostate weight into <50, 50–80 and >80 g, corresponding to small, moderate and large glands, respectively. Perioperative data and the histopathological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…And then, we eliminated 153 studies based on screening the titles and abstract. After full‐text assessing of 45 studies were performed, eventually 22 studies (Allaparthi, Hoang, Dhanani, & Tuerk, ; Butow et al, ; Caliskan, Kaba, Koca, & Ozturk, ; Chang, Moon, Gianduzzo, & Eden, ; Chu et al, ; Descazeaud, Zerbib, Vieillefond, Debre, & Peyromaure, ; Foley, Bott, Thomas, Parkinson, & Kirby, ; Freedland et al, ; Galfano et al, ; Goetzl, Krebill, Griebling, & Thrasher, ; Hong et al, ; Kim et al, ; Labanaris et al, ; Lallas et al, ; Levinson et al, ; Marchetti, Shikanov, Razmaria, Zagaja, & Shalhav, ; Msezane et al, ; Olsson et al, ; Pettus et al, ; Yadav et al, ; Yasui et al, ; Zorn et al, ) were enrolled in our meta‐analysis. The characteristics of them were introduced in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And then, we eliminated 153 studies based on screening the titles and abstract. After full‐text assessing of 45 studies were performed, eventually 22 studies (Allaparthi, Hoang, Dhanani, & Tuerk, ; Butow et al, ; Caliskan, Kaba, Koca, & Ozturk, ; Chang, Moon, Gianduzzo, & Eden, ; Chu et al, ; Descazeaud, Zerbib, Vieillefond, Debre, & Peyromaure, ; Foley, Bott, Thomas, Parkinson, & Kirby, ; Freedland et al, ; Galfano et al, ; Goetzl, Krebill, Griebling, & Thrasher, ; Hong et al, ; Kim et al, ; Labanaris et al, ; Lallas et al, ; Levinson et al, ; Marchetti, Shikanov, Razmaria, Zagaja, & Shalhav, ; Msezane et al, ; Olsson et al, ; Pettus et al, ; Yadav et al, ; Yasui et al, ; Zorn et al, ) were enrolled in our meta‐analysis. The characteristics of them were introduced in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies indicated that patients with lower PWs had a significant increase in PSMs (Chu et al, ; Labanaris, Zugor, & Witt, ; Zorn et al, ). However, other two studies did not find the significant association between PW and PSMs (Olsson et al, ; Yasui et al, ).…”
Section: Introductionmentioning
confidence: 90%
“…The accuracy of the methods used for measuring the whole gland volume has been recently reviewed, and imaging has proven more accurate than digital rectal examination, particularly mpMRI 14,15 . The volume of the whole gland has been associated with oncological outcomes, but the TV is usually only a small proportion of the whole gland 16–17 . If the optimal method for measuring the TV could be identified, the prognostic potential of TV measurement may become clearer.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the volume of the prostate gland (PGV) can be performed by a variety of methods and has many clinical purposes. [1][2][3] In general practice it can be relevant as part of the assessment of a patient with urinary symptoms. It is used to assess suitability for and response to treatment including 5 alpha-reductase inhibitors in benign prostatic hypertrophy (BPH) and the likelihood of developing urinary retention.…”
Section: Introductionmentioning
confidence: 99%
“…Recent large studies have confirmed an association between PGV and a range of pathological and functional outcomes after prostatectomy, including the likelihood of positive margins and incontinence. 2,3 For radiation oncologists it may be used to determine the number of brachytherapy seeds to order.…”
Section: Introductionmentioning
confidence: 99%